A phthalimide-based fluorescent probe for thiol detection with a large Stokes shift1. Issue 24 (15th March 2015) - Liu, Xingjiang; Gao, Li; Yang, Liu; Zou, Lifen; Chen, Wenqiang; Song, Xiangzhi
<x xml:space="preserve">Abstract</x> A phthalimide-based fluorescent probe for thiols with a large Stokes shift (161 nm) was developed via PET and ESIPT mechanisms. This probe displayed good selectivity and high sensitivity toward thiols. Imaging intracellular thiols was successfully achieved in living cells.